2016
DOI: 10.1016/j.jvs.2015.12.028
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting reinterventions after open and endovascular aneurysm repair using the St George's Vascular Institute score

Abstract: The SGVI score appears to be a useful tool to predict reintervention risk in patients after open repair and EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…A direct relationship between the studied scores and costs is not shown. Large trials for the validation of SGVI scoring for reinterventions has been reported recently (De Bruin et al, 2016;A Karthikesalingam et al, 2015). Our data correlate with these studies and additionally reveals that the SGVI score can estimate the expenses of a hospital for the initial procedure and overall intervention costs.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A direct relationship between the studied scores and costs is not shown. Large trials for the validation of SGVI scoring for reinterventions has been reported recently (De Bruin et al, 2016;A Karthikesalingam et al, 2015). Our data correlate with these studies and additionally reveals that the SGVI score can estimate the expenses of a hospital for the initial procedure and overall intervention costs.…”
Section: Discussionsupporting
confidence: 82%
“…SGVI score was also tested in the outcomes of open surgery and was found related to higher complications following open repair but half of them were wound complications which are not comparable with catastrophic long term aortic complications of EVAR (De Bruin et al, 2016). It should be stated that high risk in the SGVI score can warn the surgeon to either reassess open surgery or if it is still necessary the health care providers and assurance system should be aware of higher index operation costs and reinterventions of EVAR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,26,27 Other studies, however, highlight the importance of preoperative anatomy in predicting the reintervention risk, for instance by applying the St George’s Vascular Institute Score, or by treating patients according to instructions for use (IFU). 28,29…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with connective tissue disorders and anomalous arch anatomy appear to be susceptible. 1 As endovascular techniques continue to evolve, these patients can now be treated with advanced endovascular technologies. Herein, the case of a woman with a bovine arch and history of prior cardiovascular surgery for a type A dissection who returned 2 months later with a new descending thoracic aortic aneurysm and type B dissection is presented.…”
Section: Introductionmentioning
confidence: 99%